PENGARUH MODEL PEMBELAJARAN SENTRA TERHADAP MOTIVASI BELAJAR ANAK USIA 5-6 TAHUN DI TK ANNISAH HUSNAH KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Rizki Wulandari Rizki Wulandari; Ria Novianti Ria Novianti; Enda Puspitasari Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrct: The research is to know the influence of learning model centers to learning motivation of Children 5-6 years children Annisah Husnah kindergarten District of Tambusai Utara Rokan Hulu Regency. The sample of population in this is 5-6 years children at Annisah Husnah kindergarten to 30 amount persons. To collect observtion and skala likert in interview seacion. Analysis data use corelation and analysis statistic method with SPSS for windows version 16. The technich analysis data used the pearson product moment formula. The result used Pearson Product Moment correlation analysis there is a positive relationship between learning model centers on learning motivation of 5-6 years children at Annisah Husnah kindergarten District of Tambusai Utara Rokan Hulu Regency. It can be seen from the acquisition value of the correlation coefficient of rxy = 0.608 with probability is 0,001. There fore p<0.05 (0.001<0.05). The level of relationship between the of learning model centers with learning motivation of children in the strong category with determinant coefficient value is generated is equal KP = r² x 100% = 37% means is the learning model centers accounted for 37% child motivation learn and the reminder 63% is affected by other variables.Key words : Learning model centers , Learning motivation